Relief from intractable phantom pain by combining psilocybin and mirror visual-feedback (MVF). Issue 2 (4th March 2018) - Ramachandran, Vilayanur; Chunharas, Chaipat; Marcus, Zeve; Furnish, Timothy; Lin, Albert
ABSTRACT: AL's leg was amputated resulting in phantom-limb pain (PLP). (1) When a volunteer placed her foot on or near the phantom – touching it evoked organized sensations in corresponding locations on AL's phantom. (2) Mirror-visual-feedback (MVF) relieved PLP, as did, "phantom massage". (3) Psilocybin-MVF pairing produced synergistic effects, complete elimination of PLP, and reduction in paroxysmal episodes. (4) Touching the volunteer's leg where AL previously had external fixators, evoked sensation of nails boring through the leg. Using a "telescoping" nail, we created the illusion of a nail being removed with corresponding pain relief. (5) Artificial flames produced warmth in the phantom.